Editorial - Alberca-Sialer, Fabrizio Augusto (2024)
The journal Turismo y Patrimonio presents its 23rd issue. In this edition, readers will find eight articles. Of these, six have cultural heritage as their central axis and tourism as a form of use that must inevitably be sustainable. The other two articles develop business issues linked to tourism and hospitality, including sustainability as a complementary topic.